Characteristics of Dr. Mahmoud Al-Bustani’s structural approach to the Qur’anic text - Al-Hamidawi, Muhammad (Al-Adab Journal, 2024)
The study at hand dealt with research into the characteristics of Dr. Mahmoud Al-Bustani’s constructivist approach and the features that distinguished that approach from other approaches that attempted to clarify the organic unity of the Qur’anic text. It alluded to the theoretical components of that approach and its distribution between a religious heritage, data from psychological schools, and modern literary techniques, and demonstrated his visions. Concerning reading and its controls, it shed light on his reservations towards ancient rhetoric and clarified his perceptions of the typical rhetorical approach, and his belief in the relativity of rhetorical principles Which in turn leads to saying that the rhetorical miracle of the Qur’an remains open, and is not determined by the principles of this generation or that. Rather, there always remain other principles, which may be uncovered through the process of discovery practiced by each generation. The study found that the most apparent features of Al-Bustani’s constructivism lie. In singling out a distinct position for the recipient, the concept presented by Al-Bustani about (receiving) can be considered an isthmus between the direction of negative reception, which makes the recipient an element of consumption and emotion, and the direction, which makes the recipient (creative) and a contributor to the production of the text.The study found that Mahmoud Al-Bustani finds no objection to adopting the common human tributaries in the issue of reading, as long as Islam does not set detailed rules for (reading) and prevents anyone from transgressing them. This means that it leaves, within certain conditions, a large space for human experience and expertise in creating a curriculum. (Reading), takes into account a number of determinants, and it follows that any approach that undertakes to read the Qur’anic text will impose its justifications and gain its legitimacy, regardless of the nature of the approach and its approach in dealing with the text and uncovering its characteristics, while remembering the necessity of that approach being the product of principles. Considerable scientific or artistic, and in so far as the issue does not lead to chaos and absurdity in understanding or contradicting the purpose that the religious text wants to convey to people.